Flexible ERP for Construction Company with Petri Net Model - Masca Indra Triana; Berlian Al Kindhi (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2020)
Prospectively, the existence of the construction service industry, both small and large scale, has strategic value for Indonesia, considering that the proportion of its role is quite large and involves the large number of workers involved in the implementation of a construction project. From the above statement, it can be concluded that construction service companies have a positive impact on economic development. But in reality, the implementation of a construction service business has several obstacles and problems. According to the Report on Construction Development "BAPEKIN" in the socialization of Law no. 18/1999 and the Implementation Regulations for construction services, there are several problems that occur in the Business Potential or Conditions of Construction Services in Indonesia. Generally, these problems are the unrealized quality of construction, timeliness of implementation, and efficiency of resource utilization as planned. The unequal position between Service Users and Service Providers in rights and obligations is fair and harmonious. To overcome the above problems, one solution is to develop a technology that can integrate the needs of various construction companies, facilitate the company's business processes so that the company's goals can be maximally achieved. ERP is an enterprise information system designed to coordinate all resources, information, and activities required for a complete business process. ERP systems are based on databases and modular software designs.